Simulating the exchange of Majorana zero modes with a photonic system - Jin-Shi Xu (Nature Portfolio, 2016)
Majorana zero modes are a potential resource for quantum information processing as they offer immunity to noise, but they are difficult to create and control experimentally. Here, the authors use a photonic quantum simulator to mimic the exchange of Majorana zero modes in a spin-half chain.